Awdijowy korpus maminorěcneje dolnoserbšćiny ako žrědło za pśeslěźowanje dolnoserbskeje dialektalneje frazeologije - Kaulfürst, Fabian (Słowiańska frazeologia gwarowa II, 2020)
THE TEXT AND SPEECH CORPUS OF NATIVE LOWER SORBIAN AS A SOURCE FOR RESEARCH ON LOWER SORBIAN DIALECTAL PHRASEOLOGYThis paper deals with the (dialectal) phraseology of Lower Sorbian, a highly endangered language currently spoken by fewer than 500 native speakers. It first introduces the Language Portal of the Cottbus department of the Sorbian Institute dolnoserbski.de. It goes on to present one module of this portal as a resource for linguistic research: a text and speech corpus of native Lower Sorbian containing 100 hours of speech recordings of the last generation of native (mostly dialect) speakers that have been transcribed and subsequently translated into German. These recordings can therefore be searched/accessed in both languages. In some selected parts a translation into English and a phonetic transcription using International Phonetic Alphabet (IPA) is also available. In order to demonstrate the value of this material for phraseological studies and to stimulate further research, this paper then quotes selected phraseologisms from one of these recordings. Many of them have not yet been lexicographically registered. As this paper shows, the direct use of phraseological units of German origin is a special feature of such dialectal texts and, more generally, that the use of phraseologisms in bilingual or multilingual contexts is a promising field of research in linguistics.